(untitled) (SCIENCE TIME JOURNAL, 2026)
Jumping ability and explosive strength are fundamental performance factors in volleyball, directly influencing attacking, blocking, and serving efficiency. This article investigates the role of structured physical training methods, particularly plyometric and strength-based exercises, in improving these abilities among volleyball players. The study synthesizes current scientific literature and proposes an effective training model aimed at developing lower-body power, neuromuscular coordination, and vertical jump performance. The findings suggest that combined plyometric and resistance training significantly enhances explosive strength and jump height, thereby improving overall volleyball performance.